THE DEVELOPMENT RESEARCH OF THE FISHING BOAT DISTINCTION TECHNIQUE BY SATELLITE-ONBOARD HIGH RESOLUTION OPTICAL SENSOR — DISTINCTION TECHNIQUE USING IKONOS DATA - - T. MORIYAMA; - H. TAMEISHI; - J. SUWA; - S. KANNO; - Y. SUGIMORI; - T. OSAWA; - M. KOIWA (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2004)
This paper describes the vessel distinction algorithm by using radiance silhoutte algorithm for IKONOS data. Although original TKONOS image has high spatial resolution about 1 m, it is difficult to identify whole feature of the vessel. The newly developed algorithm named "Radiance Silhoutte Analysis Algorithm" can estimate entire length, full width and bridge location of the vessel in high accuracy. By using targeted vessels, it is evaluated the algorithm has sufficient accuracy for vessel distinction. The research also covers synthetic collation decision by using vessel type axtraction algorithm. Keyword: IKONOS image, SPOT, ALOS image, high resolution image alogarithm, nearest neighbor interpolation, cubic convolution interpolation